Metallothionein isogene transcription in red blood cell precursors from human cord blood - Rahman, Mohammad Tariqur; De Ley, Marc (Federation of European Biochemical Societies, 2001)
The in vitro transcription patterns for 10 functional metallothionein (MT) isogenes have been investigated in red blood cell (RBC) precursors from human cord blood. Active transcription status of the isogenes, MT-0, MT-1A, MT-1B, MT-1E, MT-1G, MT-1X, and MT-2A, was detected in both ex vivo expanded RBC precursors (burst-forming unit-erythroid) and glycophorin A1 and CD711 cells separated by magnetic cell sorting. Transcription patterns of these isogenes were analyzed at different times of incubation with the addition of Zn supplement. In neither the ex vivo expanded precursors nor glycophorin A1 and CD711 cells could MT-1F and MT-3 be detected. Transcripts of MT-4 were detected in glycophorin A1 and CD711 cells. Erythropoietin-responsive constitutive transcriptionof MT-1X and possible interleukin-3-responsive downregulation of MT-2A in ex vivo expanded precursors reveal their effect on MT biosynthesis. Biosynthesis and induction of MT at the protein level in the RBC precursors was also demonstrated by immunoblotting. Keywords: erythropoietin; glycophorin A; interleukin-3; metallothionein; zinc status.